2019
DOI: 10.1038/s41684-019-0288-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiments done in Black-6 mice: what does it mean?

Abstract: Low replicability of animal experiments is perceived as a major hurdle in the field of biomedicine. Attempts to enhance the replicability and to reduce the variability in basic research has led to a recommendation to use isogenic mice. The C57BL/6 strain has evolved as a gold standard strain for this purpose. However, the C57BL/6 mice are maintained as sub-strains by multiple vendors. Evidence exists that the subtle differences between these mouse lines have not been systematically investigated and are often i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 99 publications
2
30
0
2
Order By: Relevance
“…The AB strain is among the most common lab strains used. Since AB fish often are bred at different facilities, differences between fish from different facilities can be expected to the same extent as those described in rodents from different vendors (Palm et al, 2011a,b, 2012; Goepfrich et al, 2013; Momeni et al, 2015; Åhlgren and Voikar, 2019). Considering the different tests used, fewer differences were revealed using the scototaxis test.…”
Section: Discussionmentioning
confidence: 95%
“…The AB strain is among the most common lab strains used. Since AB fish often are bred at different facilities, differences between fish from different facilities can be expected to the same extent as those described in rodents from different vendors (Palm et al, 2011a,b, 2012; Goepfrich et al, 2013; Momeni et al, 2015; Åhlgren and Voikar, 2019). Considering the different tests used, fewer differences were revealed using the scototaxis test.…”
Section: Discussionmentioning
confidence: 95%
“…A multitude of studies have shown significant effects of background strain on specific behaviors, such as tests of baseline activity level and even complex learning tasks. 23 As such, it is conceivable that the lack of findings in the previous paper may not generalize to the strain used in the present study (ie, FVB). 22 Moreover, even substrains of the same background strain (ie, C57BL/6J and C57BL/6N) show significant differences on a battery of tests.…”
mentioning
confidence: 73%
“…22 Moreover, even substrains of the same background strain (ie, C57BL/6J and C57BL/6N) show significant differences on a battery of tests. 23 As such, it is conceivable that the lack of findings in the previous paper may not generalize to the strain used in the present study (ie, FVB). Moreover, it is important to consider other variables of vocalization production, such as call-type utilization profiles, or spectral parameters like fundamental frequency and amplitude.…”
mentioning
confidence: 73%
“…Therefore, even subtle and inevitable changing experimental conditions may lead to completely contradicting conclusions about the treatment under investigation (in our case strain differences). This might even occur when an experiment is replicated in the same laboratory, but for example the animals are purchased by another vendor 47 , tested by another experimenter 48 or at another time of the day 34 . In line with these examples, 50% of interviewed scientists stated they have experienced failures in replicating their own experiments 5 .…”
Section: Discussionmentioning
confidence: 99%